Thickness dependent penetrant gas transport properties and separation performance within ultrathin polysulfone membrane: Insights from atomistic molecular simulation - Lock, S.S.M. (John Wiley and Sons Inc., 2018)
Simulation technique has been employed to elucidate the effect of thickness upon confinement to gas transport properties in pure and binary mixtures within ultrathin polysulfone membranes. It is found that the gas diffusivity, solubility, and permeability are improved with increment in membrane thickness, which can be rationalized through bigger free volume in thicker polymeric membranes attributed to diminishing chains relaxation. The effect is found to be exceptionally perceptible in thinner polymeric films beneath 400 Ã . Accuracy of the simulation methodology has been validated by demonstrating good accordance with actual gas permeability data. As for binary condition, the gas transport properties are demonstrated to be comparatively lower than its pure counterpart due to competitive sorption and barrier for diffusion in the presence of secondary gas molecules. In addition, quantitative re-evaluation of published correlations and establishment of new empirical models have been conducted to associate membrane thickness effect to gas transport characteristics. Â© 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2018, 56, 131â158. Â© 2017 Wiley Periodicals, Inc.